Spatial Lead Pollution in Aquatic Habitats and the Potential Risks in Makassar Coastal Area of South Sulawesi, Indonesia - Mallongi, Anwar; Ane, Ruslan La; Birawida, Agus Bintara (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2017)
Background: Lead can be a poison to the environment which may affects all body systems. Lead can also affect human health especially children, lead potentially lowering level of intelligence, growth, loss, causing anemia, and disorder among children as lead is neurotoxin and accumulative. In addition lead can cause a decrease in the ability of the brain, whereas in adults may cause interference of high blood pressure and other tissue toxicity. Any increase in the levels of lead in the blood of 10 ug / dl led to a decrease in IQ of 2.5 points or 0.975 IQ. The research aims to produce a special model of health risk among elementary school children due to lead exposure in the coastal city of Makassar.Methods: This study investigate the distribution of toxic lead in Makassar coastal area namely; sea water, sediments, shells and crab. Then investigate lead toxins around the school such as lead in soil, dust, paint, snacks and air. After create distribution maps lead risks we create analysis of environmental health risks for children.Results: Result revealed that the analysis of spatial distribution of Lead in the sediment shows that the high distribution was in station 3 in Mariso districts then coastal Tallo area and the lowest was in Tamalate District. While the analysis of the spatial Pb distribution in mussels seen that the highest distribution Pb was in station 4 of districts Mariso then coastal waters Tallo area and the lowest was in Tamalate District 5.00 to 7.20 mg / g.Conclusion: In conclusion, it revealed the concentration of Lead at all stations of those four districts have exceeded the level of allowed standard and may potentially lead to a hazard both to environment and human being who are living in the surround area.